Save the Syrian Heritage: technologies to document Palmyra and endangered world heritage Interview to Yves Ubelmann, Iconem’s CEO - MediaGEO, Redazione (Archeomatica, 2018)
An interview to ICONEM on the role of digital technologies used to preserve endangered cultural heritage, with a particular eye on syrian cultural heritage. Still at the moment the French start-up is working directly on the field to preserve monuments from destructive madness of the war. In order to pursue its goals, ICONEM has gained profitable relations with Directorate General of Antiquities Museum (DGAM), which provide them all the necessary support on the territory.